2016
DOI: 10.1007/s11356-016-8045-7
|View full text |Cite
|
Sign up to set email alerts
|

First characterization of the endocrine-disrupting potential of indoor gaseous and particulate contamination: comparison with urban outdoor air (France)

Abstract: The composition of endocrine-disrupting compounds (EDCs) in the ambient air of indoor environments has already been described, but little is known about the inherent endocrine-disrupting potential of indoor air contamination. We therefore aimed to study the distribution of bioactive EDCs in the gaseous and particulate phases of indoor air using a cellular bioassay approach that integrates the interaction effects between chemicals. Organic air extracts, both gaseous and particulate, were taken from three indoor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 63 publications
1
9
0
Order By: Relevance
“…Indeed, the maximum observed effect was induced by PM 10 collected in F (wildland fire) and was equal to 1.39 luciferase activity fold induction (Figure 4a), while the standard positive curve showed a maximum effect equal to 3.54 (Figure 4f). The estrogenic activity of PM extracts, despite being low, is consistent with other studies in which an estrogenic activity was detected in PM extracts collected outdoor in urban and rural sites [20,53,[57][58][59].…”
Section: Estrogenic Activitysupporting
confidence: 91%
“…Indeed, the maximum observed effect was induced by PM 10 collected in F (wildland fire) and was equal to 1.39 luciferase activity fold induction (Figure 4a), while the standard positive curve showed a maximum effect equal to 3.54 (Figure 4f). The estrogenic activity of PM extracts, despite being low, is consistent with other studies in which an estrogenic activity was detected in PM extracts collected outdoor in urban and rural sites [20,53,[57][58][59].…”
Section: Estrogenic Activitysupporting
confidence: 91%
“…EDCs are also found in cigarette smoke and may be measured therefore in the indoor air environment where cigarettes have been smoked. As a result, many EDCs are now measurable in indoor air and in indoor dust, often at higher levels than in outdoor air 10 , 11 as discussed below.…”
Section: Sources Of Exposure To Edcs In Airmentioning
confidence: 99%
“…Studies using environmental mixtures of EDCs collected in samples of indoor air demonstrate that air does contain compounds with demonstrable estrogenic and androgenic activities when applied to in vitro assay systems. 11 However, whether the presence of these EDCs in indoor air is a specific cause of or contributes to any specific adverse human health outcome is difficult to ascertain due to the many different routes of exposure to these same compounds (diet, dermal) in addition to air.…”
Section: Effects Of Edcs In Air On Human Endocrine Healthmentioning
confidence: 99%
“…In addition, schools are important settings for the implementation of programmes that promote efforts to improve indoor air quality and behaviours that contribute to minimizing the effects of EDCs and promoting health and healthy lifestyles. Rudel et al and Oziol et al reported that EDCs concentrations are often highest indoors because many sources are indoors and can influence outdoor EDCs concentrations and because of limited degradation indoors than outdoors. Most EDCs considered in this study were synthetic organic chemicals used in a wide range of materials and goods and can be found in many products in schools, including materials used in building construction and furnishing, along with cleaning products .…”
Section: Discussionmentioning
confidence: 99%
“…We evaluated the effects of EDCs either alone or in combination, since EDCs can be released as mixtures and interact within or between classes, and combinations of low doses of EDCs that are individually inactive may cause a biological effect . According to Kortenkamp and Oziol et al , it is important to understand the effects of co‐exposure to EDCs, which may interact additively, synergistically or antagonistically, with potentially unknown intrinsic effects. The EDCs represented by PC1 (positive loadings on toluene, o‐xylene, m/p‐xylene, ethylbenzene, styrene and benzene) and PC2 (positive loadings on BHT, formaldehyde and acetaldehyde and negative loadings on cyclohexanone, benzene and benzaldehyde) showed that compounds may have different and even opposite effects, suggesting that diverse mechanisms may be involved.…”
Section: Discussionmentioning
confidence: 99%